All-optical observation of giant spin transparency at the topological insulator BiSbTe1.5Se1.5/Co20Fe60B20 interface - Suchetana Mukhopadhyay; Pratap Kumar Pal; Subhadeep Manna; Chiranjib Mitra; Anjan Barman (NPG Asia Materials, 2023)
Abstract The rise of three-dimensional topological insulators as an attractive playground for the observation and control of various spin-orbit effects has ushered in the field of topological spintronics. To fully exploit their potential as efficient spin-orbit torque generators, it is crucial to investigate the efficiency of spin injection and transport at various topological insulator/ferromagnet interfaces, as characterized by their spin-mixing conductances and interfacial spin transparencies. Here, we use all-optical time-resolved magneto-optical Kerr effect magnetometry to demonstrate efficient room-temperature spin pumping in Sub/BiSbTe1.5Se1.5(BSTS)/Co20Fe60B20(CoFeB)/SiO2 thin films. From the modulation of Gilbert damping with BSTS and CoFeB thicknesses, the spin-mixing conductances of the BSTS/CoFeB interface and the spin diffusion length in BSTS are determined. For BSTS thicknesses far exceeding the spin diffusion length, in the so-called “perfect spin sink” regime, we obtain an interfacial spin transparency as high as 0.9, promoting such systems as scintillating candidates for spin-orbitronic devices.